2016
DOI: 10.1182/blood.v128.22.1340.1340
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of PD-L1 and PD-L2 Expression By Tumor and Non-Tumor Cells in Patients with MM, MDS and AML

Abstract: Introduction:Programmed death-ligand 1 (PD-L1) contributes to tumor escape from immune surveillance by binding to programmed death-1 (PD-1), a negative regulator of T-cell responses. PD-L1 is expressed by both tumor cells and immune cells in the tumor microenvironment. In contrast, the role of PD-L2 in tumor immunity is unclear. To better understand the contribution of PD-L1/L2 to immune escape in marrow-based hematologic malignancies, we used multi-color flow cytometry and immunohistochemistry (IHC) to charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
11
1
Order By: Relevance
“…This upregulation of PD-1/PD-L1 is evident not only in the clonal cells but also in their surrounding mesenchymal cells. Dail et al [ 47 ] measured PD-L1 expression using multicolor flow cytometry and immunohistochemistry and found that PD-L1 is detectable in more than 2% of cells in all MDS patients, with the majority of expression occurring in non-tumor hematopoietic cells. This supports that the upregulation of PD-1/PD-L1 occurs in both clonal cells and MSC.…”
Section: Mds and Checkpoint Inhibitorsmentioning
confidence: 99%
“…This upregulation of PD-1/PD-L1 is evident not only in the clonal cells but also in their surrounding mesenchymal cells. Dail et al [ 47 ] measured PD-L1 expression using multicolor flow cytometry and immunohistochemistry and found that PD-L1 is detectable in more than 2% of cells in all MDS patients, with the majority of expression occurring in non-tumor hematopoietic cells. This supports that the upregulation of PD-1/PD-L1 occurs in both clonal cells and MSC.…”
Section: Mds and Checkpoint Inhibitorsmentioning
confidence: 99%
“…PD-L1, programmed death-ligand 1; PBMC, peripheral blood mononuclear cells; EGT, epigenetic therapy; AML, acute myeloid leukemia; MDS, myelodysplastic syndrome.. response to EGT, NUR77 suggesting enhanced PD-L1 expression and associated downstream molecular mechanisms may be a more potent phenotypic contributor to EGT outcomes than potential response biomarkers including NUR77. Whilst previous studies have demonstrated EGT is able to increase PD-L1 expression in MDS (16)(17)(18) and may correlate with poor responses to treatment (18) our study is the first to identify this effect independent of potential response marker expression. Whilst our in vivo observations support our in vitro findings a potential limitation of our study exists due to logistical constraints in obtaining chronologically identical patient blood samples for analysis during cycle 1.…”
Section: Discussionmentioning
confidence: 53%
“…EGT. PD-L1 reverse signaling has recently been identified as a potential mechanism of EGT resistance in the setting of MDS treatment (8,(16)(17)(18)(19). We investigated the in vitro and in vivo effect of EGT on potential down-stream effector molecules of reverse PD-L1 signaling.…”
Section: Kg-1 Cells and In Patients Non-responsive And Responsive Tomentioning
confidence: 99%
“…PD-L1 is extremely rampant in multiple myeloma (MM), myelodysplastic syndrome (MDS), and acute myelogenous leukemia (AML), with considerable expression by non-tumor hematopoietic cells, mainly CD8+ T-cells ( 23 ). PD-L2 expression is considerably absent in myeloid diseases but detectable in MM ( 24 ). Interestingly, PD-L1 expression is most common on TCs in MM and on non-tumor hematopoietic cells in MDS, while expression on non-tumor and TCs in AML was comparable ( 25 ).…”
Section: Immune Checkpoint Moleculesmentioning
confidence: 99%